2019
DOI: 10.18697/ajfand.86.17530
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dietary diversity, antenatal care, food taboos, meal frequency, and nutritional status of pregnant adolescents in rural Malawi: A cross-sectional study

Abstract: High rates of pregnancy during adolescence in Malawi compromise the nutritional status of adolescent mothers and their infants. When a pregnant adolescent is malnourished, she is at risk for health complications. Research focusing on the nutritional status of pregnant adolescents in Malawi is minimal. The purpose of this study was to assess dietary diversity, antenatal care, food taboos, meal frequency, and nutritional status of pregnant adolescents in rural Malawi. The study included sixty-two pregnant adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
1
10
2
Order By: Relevance
“…Utilisation of ANC among pregnant women in rural Malawi is at 80% [ 2 ], and of these nearly 90% receive nutrition counselling as part of this care according to the Malawian Demographic Health Survey (2015–2016) [ 33 ]. The nutrition education offered is based on the National Nutrition Guidelines [ 33 ], which note that during pregnancy, women should eat meals containing ingredients from each of the SFG and eat two extra meals per day.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Utilisation of ANC among pregnant women in rural Malawi is at 80% [ 2 ], and of these nearly 90% receive nutrition counselling as part of this care according to the Malawian Demographic Health Survey (2015–2016) [ 33 ]. The nutrition education offered is based on the National Nutrition Guidelines [ 33 ], which note that during pregnancy, women should eat meals containing ingredients from each of the SFG and eat two extra meals per day.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, there was no difference in nutrition knowledge between pregnant women attending ANC and those who did not [ 11 ]. Moreover, residing in low-resource settings women often under-utilise ANC so that those who make fewer antenatal visits are more likely to miss nutrition counselling [ 2 , 37 ]. Although ANC services remain the most accessible source for nutrition education, they may not permit the roll-out of a comprehensive nutrition education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescent pregnancy in Ghana has been linked to socio-economic status, ignorance, and their inability to access information and services related to reproductive health [ 28 ], but dietary diversity and factors associated with it among pregnant adolescents in Ghana have not been studied. Studies conducted in Bangladesh [ 29 ] and Malawi [ 30 ] reported 5.2 and 4.0 as the MDD of pregnant adolescents respectively. Whilst 70% of Malawian pregnant adolescents did not meet the MDD, only 33.3% of Bangladesh pregnant adolescents did not consume from more than five food groups.…”
Section: Introductionmentioning
confidence: 99%